Type II Crigler-Najjar syndrome: a case report and literature review - He, Tao; Geng, Xiaoling; Zhu, Lei; Lin, Xue; Wang, Lixia (Frontiers in Medicine, 2024)
Background: Crigler-Najjar syndrome (CNS) is caused by mutations in uridine 5'-diphosphate glucuronyltransferase (UGT1A1) resulting in enzyme deficiency and hyperbilirubinemia. Type II CNS patients could respond to phenobarbital treatment and survive. This study presents a rare case of type II CNS. Case summary: The proband was a 29-year-old male patient admitted with severe jaundice. A hepatic biopsy showed bullous steatosis of the peri-central veins of the hepatic lobule, sediment of bile pigment, and mild periportal inflammation with normal liver plate structure. The type II CNS was diagnosed by routine genomic sequencing which found that the proband with the Gry71Arg/Tyr486Asp compound heterozygous mutations in the UGT1A1 gene. After treatment with phenobarbital (180 mg/day), his bilirubin levels fluctuated between 100 and 200 μmol/L for 6 months and without severe icterus. Conclusion: Type II CNS could be diagnosed by routine gene sequencing and treated by phenobarbital. .